Pemeriksaan patologi anatomi pada penderita tumor di Laboratorium RSUD Hajjah Andi Depu - Nurmadina, Nurmadina; Sijid, St. Aisyah; Futriani, Futriani (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2024)
Anatomic pathology is a branch of medical science that identifies diseases through macroscopic and microscopic observation of cells, tissues, and organs. This study aims to determine the histopathological characteristics of tissues indicated to be tumors in patients examined at the Anatomic Pathology Laboratory of RSUD Hajjah Andi Depu. The research was conducted using histological methods with frozen section techniques. This process includes tissue fixation, rough and fine cutting, as well as sending samples to RSUD Pare-pare for further analysis. The results showed five types of tumors: fibroadenoma mammae sinistra, lipomatosis, cellular fibroadenoma mammae dextra, oral fibroma, and intradermal nevi. Each tumor has specific macroscopic and histopathological characteristics that provide important diagnostic information. This study confirms the role of the anatomic pathology laboratory in diagnosing diseases through tissue examination, significantly contributing to the diagnosis and clinical management process.